2011
DOI: 10.5812/kowsar.1735143x.2462
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Delta Hepatitis: A Nine-Year Retrospective Analysis

Abstract: A B S T R A C TBackground: Chronic delta hepatitis is the most severe form of viral hepatitis, for which interferon administration is the only available treatment. However, the efficacy of interferon treatment is affected by the dose and duration of treatment, and relapse rates are high. Objectives: In this study, we sought to evaluate the efficacy of treatment with pegylated interferon and observe the relapse rates of delta hepatitis after treatment. Patients and Methods: Forty-six patients with chronic delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…HDV reaches a higher prevalence between the third and fourth decades of life (7) . The average age of individuals diagnosed with hepatitis D varies between 30 and 44 years old (8,9) . Because hepatitis B is endemic in the Amazon region and often affects individuals in childhood, the disastrous consequences of association with delta virus can be noted in the second decade of life (10) .…”
Section: Discussionmentioning
confidence: 99%
“…HDV reaches a higher prevalence between the third and fourth decades of life (7) . The average age of individuals diagnosed with hepatitis D varies between 30 and 44 years old (8,9) . Because hepatitis B is endemic in the Amazon region and often affects individuals in childhood, the disastrous consequences of association with delta virus can be noted in the second decade of life (10) .…”
Section: Discussionmentioning
confidence: 99%
“…46 Selected published studies are displayed in Table 1 including patients with chronic HDV infection who were treated with pegylated interferon-alfa-based treatment for at least 48 weeks and followed up for a minimum of 6 months. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The Hepatitis Delta International Intervention Trials (HIDIT-I and HIDIT-II) explored pegylated interferon-alfa-2a either in combination with adefovir or with tenofovir for 48 or 96 weeks in patients with HDV infections. 52,56 The trials were performed in Germany, Turkey, Greece and Romania.…”
Section: Tre Atment Of Hepatitis D Virus Infec Ti On With Interferon Smentioning
confidence: 99%
“…The combination of pegylated interferon‐alfa and ribavirin for 72 weeks did not lead to an improved virological or biochemical response rate with overall poor therapy tolerance 46 . Selected published studies are displayed in Table 1 including patients with chronic HDV infection who were treated with pegylated interferon‐alfa‐based treatment for at least 48 weeks and followed up for a minimum of 6 months 45–59 …”
Section: Treatment Of Hepatitis D Virus Infection With Interferonsmentioning
confidence: 99%
“…PEG-IFN was the only available treatment that existed for HDV until recently. The evidence for this comes from a series of four randomized controlled trials and nine cohort studies [39][40][41][42][43][44][45][46][47][48][49][50][51] of HBV/HDV patients between 2006 and 2019. A recent meta-analysis by Abdrakhman et al 52 showed that PEG-IFN treatment had an estimated SVR risk difference of 0.29 [95% CI 0.24-0.34] for HDV RNA clearance over placebo, at 24 weeks off therapy.…”
Section: E Xis Ting Tre Atmentsmentioning
confidence: 99%